ANALISIS KEMASAN PRIMER PEMPEK FROZEN STUDI KASUS UMKM PEMPEK AISYAH BATURAJA - Sihombing, Tulus Martua; Adriant, Irayanti; Fadhilla, Rizka (Jurnal Bina Bangsa Ekonomika, 2025)
Pempek Aisyah is a micro, small and medium enterprise (MSME) that focuses on the production and sale of frozen pempek. This MSME was established in 2018 and is located on Jl. DR Sutomo, Baturaja Lama, South Sumatra. Pempek Aisyah MSMEs have the advantage of packaging materials that are obtained at low prices, thick materials and are not easily torn. However, Pempek Aisyah MSMEs also have a drawback in pempek wrapping, namely using ordinary vacuum plastic without a ziplock feature on the packaging, making consumers feel less effective in restoring the frozen pempek. In addition, the packaging design is less attractive and there is a lack of information on the packaging. The purpose of this research is to overcome the shortcomings in packaging to match consumer desires. If the goal has been achieved, Pempek Aisyah MSMEs will get an even wider market reach. The method used to solve the problem in this study is using the Theory U approach and the SCAMPER method. Theory U is a concept developed by Otto Scharmer, which the company uses to develop a new product and everything is purely based on what the user needs and how the user feels right now. SCAMPER is a technique of thinking with creativity with a team in terms of developing and improving products with techniques for answering seven questions from each SCAMPER letter. Based on research, it was obtained that to overcome these problems, Pempek Aisyah MSMEs design packaging according to customer wishes, namely frozen pempek packaging which has an attractive design, is environmentally friendly, has complete information and makes it easier for customers to use and store products